PEMBINAAN PEGAWAI PERPUSTAKAAN DALAM PELAKSANAAN TUGASNYA OLEH KEPALA SEKOLAH LANJUTAN TINGKAT ATAS NEGERI KABUPATEN LIMA PULUH KOTA - Ade Candra (Universitas Negeri Padang, 2015)
This article describe results of research about development of library employees by the head master of state high school in Kabupaten Lima Puluh Kota. Populationis 35 people and be population research. The research instrument uses a Likert Scale. The result showed that: 1) Development of Organization Spirit (Corps) hasa good category (4.06), 2) Development of Capability Technical Services hasan enoughcategory (3.48), 3) Development of Capabilities Reader Services hasagood category ( 3.64), 4) Development of Moral Work hasan enoughcategory (3.39),and 5) Development of Job Performance hasa good category (3.77). So, total results show development of library employees by the Head master of State senior high school inKabupaten Lima Puluh Kota has a good (3.67). Keyword :library, development, library employe